A Learning for Gifted and Talented Students in Islamic Education - Gulzhaina K. Kassymova; Mustafa Tevfik Hebebci; Mutathahirin Mutathahirin; Yerassyl K. Talgatov (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2025)
The research aims to analyze suitable learning approaches for gifted and talented students at school. A qualitative method with a